Examining the Role of Social Media and Imagined Communities in Addressing Social Welfare Gaps in Kenya - Veronica Ouya; Hawa Conteh; Njeri Kagotho (Social Media + Society)
In developing and least developed economies, traditional and spatially bound communities play a critical role in bridging the gap when formal social welfare systems fall short in meeting essential needs. While the role of traditional communities in addressing societal issues is well recognized, research on imagined communities as agents of social welfare is a new and rapidly developing area of study. This study uses the foundational tenets of Ubuntu to examine the ways in which imagined communities—influenced by social media—use their collective agency to address gaps in Kenya’s formal social welfare system. Drawing data from three storytellers’ YouTube channels, we conducted a thematic analysis of 15 personal accounts to determine how storytellers leverage their social media presence, institutional knowledge, and community trust to address gaps in an under-resourced social welfare system. Findings indicate that personal stories shared and amplified through these digital platforms resonate with the imagined community, forming emotional connections that transcend geographic and socioeconomic boundaries. We identify key actors—storytellers, beneficiaries, public institutions, and the globally dispersed imagined community—and explore how their interactions enhance community well-being. This exploration highlights the crucial role that storytelling through social media plays in mobilizing support and fostering social connections.